(untitled) (International Journal of Engineering and Computer Science, 2017)
Today many cloud users are facing the major problem of fake logging in and data theft. So it is required to authenticate the cloud user that requests access to an account for providing privacy and security. However, the techniques used for authentication so far were not capable to guarantee the same and thereby kept the data at high risk. So, we are using the concept of Biometric Authentication along with Data compression and Data Encryption. Most of the techniques of Biometric Authentication in Cloud face performance issues like time and space complexities. So it is a need to measure these flaws. This paper eventually studies all the possible techniques relevant to Biometric Authentication and upgrade the system to a new level.